The Evolution of Adolescent Sexual Practices in Indonesia: A Longitudinal Study - Rosyida, Lintang Mela; Winarni, Sri; Agushybana, Farid; Dharminto, Dharminto (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: Adolescents experience significant sexual and hormonal development, which may lead to engagement in premarital sexual practices. This study aims to analyze the factors associated with premarital sexual practices among adolescents in the 2007, 2012, and 2017 survey periods and to describe the trends and relevant variables identified in each period.Method: This longitudinal study utilized secondary data from the Indonesian Demographic and Health Survey (IDHS) on adolescent reproductive health. Respondents included unmarried adolescents aged 15–24 years who had completed the IDHS questionnaire. The sample sizes were 16,412 (2007), 16,998 (2012), and 19,970 (2017). Data analysis was conducted descriptively, followed by statistical analysis using logistic regression with a 95% confidence interval (CI).Result: The proportion of adolescents engaging in premarital sexual practices decreased slightly but not significantly: 5.8% in 2007, 5.4% in 2012, and 5.3% in 2017. Factors consistently associated with premarital sexual practices across all survey periods included sex, age, education level, knowledge of contraceptives, high-risk dating behaviors, and peer influence. Socialization through media and parental involvement are recommended strategies to prevent or delay premarital sexual practices.